Information system adoption among small medium enterprises in the Malaysian printing industry - Hiew, Tze Kong (2018)
Many researchers have acknowledged the importance of adopting the Information System (IS) to enhance an organization’s performance. In Malaysia, very few studies have examined the extent of IS adoption from a business process perspective. The objective of this study was to determine the technological, organizational and environmental factors that influence the extent of IS adoption among the small and medium sized enterprises (SMEs) in the printing industry. In addition, the moderating influence of owners/CEOs’ innovativeness in the relationship between the determinants and the extent of IS adoption was also examined. A six-factor framework of three contexts from the technological-organizational-environmental (TOE) theory was used to examine the extent of IS adoption in the business processes. The business processes examined were adapted from Porter’s business value chain. A structured questionnaire for the attention of owners/CEOs of the printing companies was used to obtain the data and measure the variables. The six independent variables examined consisted of three technological factors (relative advantage, compatibility and complexity of technology), one organizational factor (firm’s resources) and two environmental factors (customers’ pressure and competition). The dependent variable was the extent of IS adoption for business processes, measured by internal communication, internal administration, outbound communication, order-taking, inbound communication and procurement. The findings showed that resources and relative advantage influence the overall extent of IS adoption. Relative advantage and firm’s resources influence IS adoption for internal communication. Relative advantage and firm’s resources influence IS adoption for outbound communication. Firm’s resources and competition influence IS adoption of order-taking. Relative advantage, firm’s resources and customers’ pressure influence IS adoption for inbound communication. Compatibility and firm’s resources influence IS adoption for procurement. However, owners/CEOs’ innovativeness does not moderate the influence of the relationship between the antecedents and the extent of IS adoption of all the business processes.